2023
DOI: 10.1007/s11259-023-10090-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-aureus staphylococci and mammaliicocci as a cause of mastitis in domestic ruminants: current knowledge, advances, biomedical applications, and future perspectives – a systematic review

Abstract: Non-aureus staphylococci and mammaliicocci (NASM) are one of the most common causes of subclinical mastitis in dairy animals and the extent of damage by intramammary infections (IMI) caused by NASM is still under debate. The different effects of NASM on the mammary gland may be associated with differences between bacterial species. NASM are normal and abundant colonizers of humans and animals and become pathogenic only in certain situations. The veterinary interest in NASM has been intense for the last 25 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 96 publications
0
9
0
Order By: Relevance
“…NAS are increasingly reported as the most frequent isolates from lactating dairy cows ( 6 , 20 , 25 , 92 ). Some NAS are frequently reported as etiology of subclinical mastitis in dairy ruminants ( 6–9 , 93 , 94 ), while others occasionally cause mastitis in dairy cows as well as other diseases in animals ( 10–15 ). Some studies reported S. chromogenes, S. simulans , S. epidermidis, and S. xylosus as major isolates from teat skin and teat tips, whereas other studies identified S. chromogenes , S. haemolyticus , and S. xylosus as major isolates from milk samples ( 95–98 ).…”
Section: Bovine Staphylococcal Mastitismentioning
confidence: 99%
See 3 more Smart Citations
“…NAS are increasingly reported as the most frequent isolates from lactating dairy cows ( 6 , 20 , 25 , 92 ). Some NAS are frequently reported as etiology of subclinical mastitis in dairy ruminants ( 6–9 , 93 , 94 ), while others occasionally cause mastitis in dairy cows as well as other diseases in animals ( 10–15 ). Some studies reported S. chromogenes, S. simulans , S. epidermidis, and S. xylosus as major isolates from teat skin and teat tips, whereas other studies identified S. chromogenes , S. haemolyticus , and S. xylosus as major isolates from milk samples ( 95–98 ).…”
Section: Bovine Staphylococcal Mastitismentioning
confidence: 99%
“…NAS species induce only mild inflammatory response with mild to moderate increase in SCC in the infected quarter, reducing milk quality and price, and low bulk tank milk SCC may discourage producers from intervening in IMI, allowing these pathogens to cause continuous loss of productivity ( 124 , 143 , 146 ). In dairy cows with subclinical infection with these groups of pathogens at peak lactation can result in approximately 1.8 kg/d reduction in milk production ( 94 , 146 ). Because of a modest increase in milk SCC, the IMI due to NAS may not account for increased SCC in dairy farms that already have high SCC due to major mastitis pathogens.…”
Section: Bovine Staphylococcal Mastitismentioning
confidence: 99%
See 2 more Smart Citations
“…Coagulase-negative Staphylococci (CoNS) are opportunistic pathogens regularly associated with intramammary infection (IMI) in ruminants, and mostly in subclinical cases. During the last years, this group has become a main etiologic agent of ruminant mastitis [6]. Furthermore, recent studies indicate that these species are capable of causing more severe tissue damage in the mammary gland than was previously considered [7].…”
Section: Introductionmentioning
confidence: 99%